A Review Study of Eggshell Powder as Cement Replacement in Concrete - Mahmood, Lavan Jutyar; Rafiq, Serwan Khurshid; Mohammed, Ahmed Salih (Sulaimani Journal for Engineering Sciences, 2022)
The extensive usage of cement concrete leads to a 5% to 7% release of Carbon Dioxide (CO2) gas into the atmosphere resulting in increased global warming. Also, the increase in world population and industry has led to the generation of by-product waste materials such as eggshells. Landfilling non-treated eggshells sometimes cause environmental and health matters due to their odor. The use of eggshell powder as partial cement replacement is a considerable solution for recycling the waste eggshells and decreasing the cement. It is believed that eggshells powder (ESP) are rich in calcium oxide and can enhance the strength and durability of concrete. The objective of this study is to analytically review the currently available experimental studies on the effectiveness of partial replacement of ordinary Portland cement by some percentage of eggshell powders ranging between 0-25% in concrete mixes. The database was created for the concrete mixes containing eggshell powder with corresponding concrete properties such as compressive strength, flexural strength, split tensile strength, slump, and density based on nine different research groups. The results from the previous works were analyzed and discussed. The model for predicting compressive strength was established according to multilinear regression analysis using curing time, water-cement ratio, and ESP content for 92 tested data. It was concluded that eggshell powder has less strength reduction than curing time and water-cement ratio.
Keywords: Eggshell Powder; Concrete strength; Slump; Concrete Density; Statistical analysis; Modelling